Appetite-Related Hormones and Subjective Feelings of Hunger and Satiety in Adults Who Regularly Consume Dairy and Those Who Limit Dairy Consumption. (7th June 2021) - Tacad, Debra Kirsty; Krishnan, Sridevi; Cervantes, Eduardo; Horn, William; Woodhouse, Leslie; Stephensen, Charles; Keim, Nancy
Abstract: Objectives: To compare self-reported feelings of hunger and fullness with biological markers associated with appetite and satiety in men and women who are habitual dairy consumers (DC) vs limited dairy consumers (LD). We hypothesize that the DC group will have different appetite perceptions along with different concentrations of the hunger hormone, ghrelin, and the anabolic hormone, insulin, before and following a mixed meal challenge. Methods: Adults from a cross-sectional study who completed the Block food frequency questionnaire were categorized as DC ( n = 40, consumed >2 cup-eq/d of milk, yogurt, and/or cheese), or LD ( n = 37, consumed < ½ cup-eq/d of dairy). On a test day, overnight fasted and postprandial blood samples were collected after a (non-dairy) mixed meal challenge at 30 min, 3h, and 6h. Feelings of hunger, fullness, desire to eat, and prospective consumption were measured by visual analog scales (VAS) in the fasted state, and immediately following the mixed meal at 20 min, 40 min, 1h, 1.5h, 2h, 3h, 4h, 5h, and 6 h. Differences in VAS ratings, fasting glucose, insulin, and ghrelin, and 6-h incremental area under the curve (iAUC) between groups were analyzed using t-tests. Results: The DC group had lower mean fasting ghrelin ( P < 0.001) and higher fasting glucose ( P < 0.05) compared to LD. Fasting insulin levels were not different between groups ( P = 0.87), nor were there differences for 6-h iAUC for glucose, ghrelin, or insulin. Hunger, fullness, desire to eat, and prospective consumption, summarized as 6-h AUC, were not different between groups. No correlations were found between hormone concentrations and feelings of hunger, fullness, desire to eat, or prospective consumption, at fasting or 30 min, 3h or 6h following meal challenge. Conclusions: Regular consumption of ≥2 cup-eq. of dairy was associated with a reduced fasting ghrelin that might signal less hunger compared to low dairy consumers, but no relationship between ghrelin and hunger was found. The postprandial response in ghrelin, glucose, and insulin were not influenced by habitual dairy consumption. Funding Sources: Funding was provided by the United States Department of Agriculture and Arla Foods Inc.